(untitled) (Journal of Fatima Jinnah Medical University, 2023)
Background: Variation of morphology of lung fissures and lobes affects the interpretation of results of radiological examination as well as line of action in cardiothoracic surgical procedures. A research was done to find out the incidence of variations of fissures and lobes in embalmed cadaveric lungs. Materials and methods: This is a cross sectional study. All the formalin fixed lung specimens present in dissection halls and museums of the Anatomy Departments were observed for any abnormal fissures that are adding accessory lobes to lungs. Data was entered and analyzed by using SPSS 22.0. Descriptive analysis was applied by using frequencies and percentages for qualitative variables. Results: Total 80 formalin-fixed specimens of lungs were examined and a total of 29 (36.25%) (%) were found to have incomplete fissures. It was observed that 14 (17.5 %) out of 80 lungs had incomplete oblique fissures, and out of these 6 (17.65%) were found in right lungs and 08 (19.05%) were present in left lungs, whereas 15 (39.47%) right lungs showed incomplete horizontal fissure. Among 80 lungs, 6 (7.5%) presented unusual accessory fissures and lobes, whereas 5 (14.7%) showed absent horizontal fissure reducing the number of lobes to two in right lung specimen. Conclusion: There is a prevalent incidence of incomplete horizontal fissure that must be kept in mind when investigating and treating any lung pathology.